STUDI KASUS KEHILANGAN KVARH PELANGGAN TARIF I-2 DENGAN DAYA 16.500 VA DAN 17.600 VA DI PT PLN (PERSERO) AREA SEMARANG - Kartikaningtyas, Arni; Ariyanto, Eko (Vocational School Diponegoro University, 2015)
Arni Kartikaningtyas, Eko Ariyanto, in this paper explain that In electric power transmission and distribution, volt-ampere reactive (var) is the unit used to measure reactive power into AC electric power system. Reactive power in AC circuits when current and voltage are not in phase. Is a true symbol and Var, var, or VAR, but all three terms are widely used. Var terms proposed by Romanian Constantin Budeanu electrical engineer and was introduced in 1930 by the IEC in Stockholm, which has been adopted as a unit for reactive power. Var can be regarded as both the imaginary part of the apparent power, or the power flowing to the load reactive, where voltages and currents specified in volts and amperes. Two definitions are equivalent. Reactive power into the power unit kVArh is used by passive components beyond resistor which is a power loss or power that is not desirable. This power to a minimum to avoid, or at least minimized, although it will not disappear altogether, by minimizing the power factor. Industrial customers are groups of customers with the use of induction machines used for the induction process that requires a great power to drive the motor and pull out the reactive power usage needs to be taken into account. Customers I 2 is the class of tariffs for industrial purposes being at low voltage with power above 14 kVA to 200 kVA.Â Keywords: VAR, customer Industry.